Development of SETS-Based Independent Curriculum Learning Module Increases Understanding of Disaster Mitigation - Mahlianurrahman; Rapita Aprilia (Jurnal Penelitian Pendidikan IPA, 2024)
The low understanding of disaster mitigation has an impact on the high risk that victims receive. It is necessary to have an understanding of disaster mitigation from an early age. Increasing the understanding of disaster mitigation from an early age can be improved through disaster mitigation education, especially by organizing learning innovations. The learning process for disaster mitigation needs to be facilitated by teaching modules that can improve students' understanding of disaster mitigation. This study aims to describe the increase in students' understanding of disaster mitigation through the implementation of the SETS-based independent curriculum teaching modules resulting from the development. The research model used was ADDIE's research and development (R&D) model with a single-group pretest and posttest design. Product trials were carried out at Public Elementary School 2 Meurandeh and data were analyzed using the N-gain test. The results of the analysis show that students' understanding of disaster mitigation has increased with an N-gain of 78.8%. Based on the results of students' understanding of disaster mitigation scores, it can be concluded that the application of the SETS-based independent curriculum teaching module can improve elementary school students' disaster mitigation.